Physical Properties of High Performance Concrete on Base Wollastonite - Ibragim, Umbarov; Erkin, Eshquvvatov; Aziza, Kuldasheva (European Journal of Life Safety and Stability (2660-9630), 2021)
Production high-performance concrete that have to have a water/binder ratio lower then 0.40 , at the cost of this decrease porous and increase durability of matrix of cement stone, owing to their capillary and pore networks cannot be in connect to each other and this situation helps to development of self-drying. Disadvantage of high-performance concrete (HPC) compare ordinary concrete is more intensive autogenic shrinkage, which cause of micro-shrinkage cracking inside of concrete. Wollastonite can be useful in improving fire resistance of HPC which is not as perfect as that of ordinary concrete and make micro- frame inside of material. Several materials or natural minerals have been examined to make durable concrete. Wollastonite is a natural needle-crystal, as a partial substitute of binder in concrete mix at varying replacement levels 5, 10, 15%, 24 concrete sample specimens were tested at two w/b ratio (0.32 and 0.35) for physical properties which are related to durability.